2016
DOI: 10.1177/2331216515626131
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Frequency Lowering

Abstract: A novel algorithm for frequency lowering in music was developed and experimentally tested in hearing-impaired listeners. Harmonic frequency lowering (HFL) combines frequency transposition and frequency compression to preserve the harmonic content of music stimuli. Listeners were asked to make judgments regarding detail and sound quality in music stimuli. Stimuli were presented under different signal processing conditions: original, low-pass filtered, HFL, and nonlinear frequency compressed. Results showed that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Sound quality is another core criterion in evaluating patients' willingness to accept technology and degree of comfort after using it. Some researchers reported no obvious changes in soundquality ratings with or without NLFC (Uys et al, 2012;Parsa et al, 2013;Kirchberger and Russo, 2016;Tseng et al, 2018;Chen et al, 2020). Some researchers found that patients with moderate to severe sensorineural hearing loss showed a preference for listening to music with NLFC scheme (Uys et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sound quality is another core criterion in evaluating patients' willingness to accept technology and degree of comfort after using it. Some researchers reported no obvious changes in soundquality ratings with or without NLFC (Uys et al, 2012;Parsa et al, 2013;Kirchberger and Russo, 2016;Tseng et al, 2018;Chen et al, 2020). Some researchers found that patients with moderate to severe sensorineural hearing loss showed a preference for listening to music with NLFC scheme (Uys et al, 2016).…”
Section: Discussionmentioning
confidence: 99%